Pelatihan dan Pengelolaan Manajemen Event Pertandingan Bola Voli Mahasiswa PJKR Universitas Primagraha - Ariestika, Elsa; Paryadi, Paryadi; Fahmi, Fadlilah; Sari, Nugrahani Febrina; Amni, Hazrina; Febriyanto, Andita; Subagyo, Rohmad (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Volleyball match event management is an important role to provide students with the Physical Education, Health and Recreation (PJKR) study program, Primagraha University, where the output after graduating from college is not only to become a teacher, but also has other field skills such as managing sports match events. Despite the low experience and ability of students in managing match event management, training and management of match event management, especially volleyball sports, were carried out which aimed to improve event management skills among students in volleyball sports in Serang City, Banten. The methods used in this activity consisted of (1) planning stage, (2) implementation stage, (3) implementation stage, (4) evaluation stage with an observational study approach. The results of the implementation of this community service showed that the implementation of volleyball match events at the high school/vocational school level throughout Serang Raya was maximized, although it still needed significant improvement to create more volleyball events or other sports in the future. In addition, participants were enthusiastic and responded positively to this activity and understood the importance of education in managing sports match event management.